2018
DOI: 10.1002/sctm.18-0031
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous Infusion of Umbilical Cord Blood-Derived Mesenchymal Stem Cells in Rheumatoid Arthritis: A Phase Ia Clinical Trial

Abstract: Based on immunomodulatory actions of human umbilical cord blood‐derived mesenchymal stem cells (hUCB‐MSCs), in vitro or preclinical studies of hUCB‐MSCs have been conducted extensively in rheumatoid arthritis (RA). However, few human trials have investigated the outcomes of hUCB‐MSC infusions. The CURE‐iv trial was a phase I, uncontrolled, open label trial for RA patients with moderate disease activity despite treatment with methotrexate. The patients received a single intravenous infusion of 2.5 × 107, 5 × 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
87
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(91 citation statements)
references
References 44 publications
1
87
0
3
Order By: Relevance
“…Nine 2-year-cycle data from the continuous NHANES (1999-2016) were combined for analysis with greater statistical reliability (n=92 062). We excluded men (n=45 336), participants younger than 18 years (n=19 087) or older than 80 years of age (n=919), [22][23][24][25] participants who had been diagnosed with other forms of arthritis, participants with missing RA data (n=3438) or dietary magnesium information (n=9958), and 13 324 participants were eventually included in the analysis (figure 1).…”
Section: Study Populationmentioning
confidence: 99%
“…Nine 2-year-cycle data from the continuous NHANES (1999-2016) were combined for analysis with greater statistical reliability (n=92 062). We excluded men (n=45 336), participants younger than 18 years (n=19 087) or older than 80 years of age (n=919), [22][23][24][25] participants who had been diagnosed with other forms of arthritis, participants with missing RA data (n=3438) or dietary magnesium information (n=9958), and 13 324 participants were eventually included in the analysis (figure 1).…”
Section: Study Populationmentioning
confidence: 99%
“…Evaluation of BM-MSC therapy on the healing of joints in animals with induced RA demonstrated that inflammation, joint swelling, and destruction of cartilage reduced significantly compared with an arthritic non-treated group [ 223 ]. Park and coworkers in the first human trial of hUCB-MSCs in patients with RA observed no major toxicity, serious adverse event, or major abnormalities in serum chemicals or hematologic profiles, both during and after the treatment [ 224 ]. Allogenic UC-MSCs transplantation in mice model of RA prevented arthritis progression by suppressing T follicular helper (Tfh) cells proliferation [ 220 ].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, a possible therapeutic approach that is beginning to be explored is the use of mesenchymal stromal/stem cells (MSCs), which have already shown evidences of clinical improvements in other autoimmune diseases, namely, systemic lupus erythematosus (X. Li, Wang, Liang, Zhang, & Sun, ; Liang et al, ; Wang et al, ) and multiple sclerosis (Connick et al, ; Karussis et al, ). Recently, clinical trials, using umbilical cord blood (UCB)‐derived (Park et al, ) and bone marrow (BM)‐derived MSC (Ghoryani et al, ) for the treatment of RA patients, demonstrated that MSC‐based therapy reduced DAS28 score, decreased the percentage of peripheral blood (PB) Th17 cells and serum levels of IL‐1β, IL‐6, IL‐8, and TNFα, while increasing PB regulatory T (Treg) cells percentage and IL‐10 in serum. These clinical trials showed evident clinical benefits for the RA patients under MSCs treatment (Ghoryani et al, ; Park et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, clinical trials, using umbilical cord blood (UCB)‐derived (Park et al, ) and bone marrow (BM)‐derived MSC (Ghoryani et al, ) for the treatment of RA patients, demonstrated that MSC‐based therapy reduced DAS28 score, decreased the percentage of peripheral blood (PB) Th17 cells and serum levels of IL‐1β, IL‐6, IL‐8, and TNFα, while increasing PB regulatory T (Treg) cells percentage and IL‐10 in serum. These clinical trials showed evident clinical benefits for the RA patients under MSCs treatment (Ghoryani et al, ; Park et al, ). MSCs have also provided promising results in collagen‐induced arthritis in mice, wherein MSC treatment delayed the disease onset, reduced the paw swelling and the infiltration of immune cells into the joints, and abolished the arthritis progression.…”
Section: Introductionmentioning
confidence: 99%